On a Conjecture of Zheng Jianhua - Wu, Zhaojun (Sarajevo Journal of Mathematics, 2024)
In this paper, a new proof of the existence of the T direction is given. Furthermore, we prove that for a meromorphic function f with finite lower order, satisfying _r→ ∞ T(r,f)^2r=∞, there exists a T direction concerning small functions. 1991 Mathematics Subject Classification. Primary 30D30, Secondary 30D35